Kepemimpinan Transformasional sebagai Kepemimpinan Dakwah - Allolangi, Yusuf Rahmat (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2012)
There are two paradigms we can found when discussing about leadership; those are transactional and transformational leadership. This paper is to examine the contribution of transformational leadership to commitment and its concomitants of involvement, loyalty, and satisfaction. I also consider the mechanisms underlying the process. Although transformational leadership clearly affects the performance of work groups and organizations, the strongest effects of transformational leadership seem to be on followersâ attitudes and their commitment to the leader and the organization. Moreover, it may be that it is the extraordinary commitment of followers of transformational leaders that underlies the exceptional performance of many groups led by transformational leaders.